Molecular characterization and bioactive potential of newly identified strains of the extremophilic black yeast Hortaea werneckii isolated from Red Sea mangrove - Mohamed Salah El-Din Hodhod; Abdel-Rhman Zakaria Gaafar; Aref Alshameri; Ahmed Ali Qahtan; Abdulrahman Noor; Mohamed Abdel-Wahab (Biotechnology & Biotechnological Equipment, 2020)
The adaptations that halophilic microorganisms have developed due to their extreme habitat, promote the production of active natural compounds with the potential to control microorganisms causing infections associated with health care. The prime purpose of this study was to isolate and identify extremophilic black yeast Hortaea werneckii from intertidal decayed leaves of Avicennia marina located on the Red Sea Coast of Saudi Arabia and to evaluate the antibacterial activity of the crude extract against both gram-positive and gram-negative pathogenic strains. Three new H. werneckii strains with distinguished morphological features, MF135, MF140 and MF141, were isolated and were placed in a monophyletic clade through phylogenetic analysis based on the large subunit ribosomal ribonucleic acid (LSU rRNA). The ethyl acetate crude extract active fractions of these strains possessed significant activities against Methicillin-resistant Staphylococcus aureus (MRSA), Campylobacter jejuni and Salmonella typhimurium. The gas chromatography–mass spectrometry analysis of the active fractions revealed the presence of antimicrobial-related biochemicals, i.e. 4-Acetoxy-2-azetidinone, sec-Butyl nitrite and Fatty Acid Methyl Ester (FAME). This is the first detailed report of black yeast detected with potential antibacterial activity against various pathogenic microorganisms. These results promise potential and interesting biotechnological tools to overcome the staggering problem of emerging antibiotic resistance among pathogenic bacteria.